MANAGING CONSUMER COMMITMENT THROUGH ONLINE BRAND COMMUNITIES: EMPIRICAL EVIDENCE FROM CHINA - Zhang, Jing; Shabbir, Rizwan; Pitsaphol, Chatchai; Hassan, Waseem (European Scientific Journal, ESJ, 2015)
The competitive virtual environment generates opportunities for organizations to secure ever-lasting relationship with consumers. This study revealed the relationship of perceived benefits and community commitment enjoyed by the consumers after joining online brand community. A sample of 308 respondents is obtained from China through social networking sites. The analytical outcome highlights the decisive role of hedonic, learning, selfesteem and social benefits for enhancing brand community commitment. Moreover, consumer knowledge before joining a brand page was investigated which concluded that consumer commitment is not moderated by consumer knowledge in an online brand community but it showed positive impact as an antecedent of community commitment. Brand managers could use this accessible tool for satisfying consumer needs and for enhancing brand attachment and loyalty. The future studies might investigate the impact of such consumer commitment on brand loyalty and brand equity by emphasizing on management perspective.